A soybean sodium/hydrogen exchanger GmNHX6 confers plant alkaline salt tolerance by regulating Na+/K+ homeostasis - Jin, Ting; An, Jiaxin; Xu, Huadong; Chen, Jie; Pan, Lang; Zhao, Ranran; Wang, Ning; Gai, Junyi; Li, Yan (Frontiers in Plant Science, 2022)
Alkaline soil has a high pH due to carbonate salts and usually causes more detrimental effects on crop growth than saline soil. Sodium hydrogen exchangers (NHXs) are pivotal regulators of cellular Na+/K+ and pH homeostasis, which is essential for salt tolerance, however, their role in alkaline salt tolerance is largely unknown. Therefore, in this study, we investigated the function of a soybean NHX gene, GmNHX6, in plant response to alkaline salt stress. GmNHX6 encodes a Golgi-localized sodium/hydrogen exchanger, and its transcript abundance is more up-regulated in alkaline salt tolerant soybean variety in response to NaHCO3 stress. Ectopic expression of GmNHX6 in Arabidopsis enhanced alkaline salt tolerance by maintaining high K+ content and low Na+/K+ ratio. Overexpression of GmNHX6 also improved soybean tolerance to alkaline salt stress. A single nucleotide polymorphism in the promoter region of NHX6 is associated with the alkaline salt tolerance in soybean germplasm. A superior promoter of GmNHX6 was isolated from an alkaline salt tolerant soybean variety, which showed stronger activity than the promoter from an alkaline salt sensitive soybean variety in response to alkali stress, by luciferase transient expression assays. Our results suggested soybean NHX6 gene plays an important role in plant tolerance to alkaline salt stress.